The Power of Social Attribution: Perspectives on the Healing Efficacy of Ayahuasca - Brabec de Mori, Bernd (Frontiers in Psychology, 2021)
During the last decades, ayahuasca gained much popularity among non-Indigenous and out-of-Amazonia based populations. In popular culture, it has been advertised as a natural remedy that was discovered by Indigenous peoples ante millennia and that has been used for shamanic healing of all kinds of ailments. This “neo-shamanic”, and often recreational, use of ayahuasca, however, has to be distinguished from traditional Indigenous praxes on the one hand, and, on the other, from medical investigation in the modern world. The former, Indigenous use mainly understands ayahuasca as an amplifying power for interacting with non-human beings in the animal, plant, or spirit realms. Within this paradigm, efficacy is not dependent on the drug, but on the correct communication between the healer (or sorcerer) and the non-human powers that are considered real and powerful also without resorting to ayahuasca. The latter, modern mode of understanding, contrastingly treats the neurochemical processes of MAO inhibition and dimethyltryptamine activity as trigger mechanisms for a series of psychological as well as somatic responses, including positive outcome in the treatment of various mental conditions. I argue that there is an ontological incommensurability occurring especially between the Indigenous and medicinal concepts of ayahuasca use. Modern medical applications of ayahuasca are so fundamentally different from Indigenous concepts that the latter cannot be used to legitimate or confirm the former (and vice versa). Finally, the deep coloniality in the process of appropriation of the Indigenous by the modern has to be questioned and resolved in any case of ayahuasca application.